What have we learnt from the clinical outcomes trials with the cetrapibs?. Issue 4 (August 2018) - Doggrell, Sheila A.
Abstract : Purpose of review: The current review considers what we have learnt from the clinical outcome trials with the cetrapibs; the inhibitors of cholesteryl ester transfer protein that increase HDL cholesterol levels; torcetrapib, dalcetrapib, evacetrapib and anacetrapib. Recent findings: Although an off-target increase in blood pressure may have contributed to the failure of torcetrapib in Investigation of Lipid Level Management to Understand its Impact in Atherosclerotics Events, recent evidence shows that torcetrapib also increased atherogenic apoproteins, and this may have contributed to its failure. Evacetrapib and anacetrapib also increase atherogenic apoproteins. This may have contributed to lack of effect of evacetrapib in Assessment of Clinical Effects of Cholesteryl Ester Transfer Protein Inhibition with Evacetrapib in Patients at a High Risk for Vascular Outcomes. The success of anacetrapib in Randomized Evaluation of the Effects of Anacetrapib through Lipid Modification is more likely to have been due to lowering LDL cholesterol than to increasing HDL cholesterol. The lack of potency in increasing HDL cholesterol was initially considered as a reason for the failure of dalcetrapib in dal-OUTCOMES, but recent genomic studies suggest that dalcetrapib may be effective in subjects with a particular genotype, and this is being clinically tested. Summary: Collectively, these clinical outcome trials do not support raising HDL cholesterol by inhibiting cholesteryl ester transfer protein, as a mechanism for improving cardiovascular outcomes, in the total population of subjects with coronary artery disease.